Pemberian Remisi Terpidana Korupsi: Perlindungan Asasi atau Diskriminasi - Revando Syahaqul Husna (UIN Sunan Kalijaga Yogyakarta, 2023)
This research puts the issue of granting remissions to corruption convicts which began with the stipulation of PP No. 99 of 2012 concerning Terms and Procedures for the Implementation of the Rights of the Fostered Citizens, it is necessary to have the conditions met first so that in the end the remission can be granted. In fact, the problem of abolishing remissions is not a form of discrimination against the rights of convicts, especially those convicted of corruption, but rather a form of restriction for convicts of corruption so that they do not arbitrarily use their remission rights. The results obtained in this study are the enactment of restrictions on the rights of corruption convicts through strict remission requirements. Through a normative approach, the author explores information through statutory regulations and the regulations under them, namely through Law no. 22 of 2022 and PP No. 99 of 2012.Penelitian ini meletakkan isu pemberian remisi kepada terpidana korupsi yang bermula pada penetapan PP No. 99 Tahun 2012 Tentang Syarat dan Tata Cara Pelaksanaan Hak Warga Binaan maka perlu adanya syarat yang dipenuhi terlebih dahulu sehingga pada akhirnya remisi tersebut dapat diberikan. Sejatinya problematika penghapusan remisi ini bukanlah sebagai bentuk diskriminasi terhadap hak narapidana khususnya terpidana korupsi, melainkan bentuk pembatasan bagi terpidana korupsi agar tidak semena-mena menggunakan hak remisi tersebut. Adapun hasil yang didapat pada penelitian kali ini adalah berlakunya pembatasan hak terpidana korupsi melalui syarat ketat keberlakuan remisi. Melalui pendekatan normatif, penulis menggali informasi melalui peraturan perundang-undangan beserta peraturan di bawahnya yakni melalui UU No. 22 Tahun 2022 dan PP No. 99 Tahun 2012.